Mathematics Teachers' Knowledge, Networks, Practice, and Change in Instructional Visions. (May 2021) - Munter, Charles; Wilhelm, Anne Garrison
An instructional vision is the discourse that teachers or others currently employ to characterize the kind of "ideal classroom practice" to which they aspire but have not yet necessarily mastered. In mathematics education, prior work has demonstrated relations between teachers' instructional vision and a variety of aspects of their classroom practice and professional pursuits. We examined what might contribute to teachers' development of mathematics instructional visions through a quantitative analysis of a longitudinal data set collected in four urban school districts. Controlling for instructional vision in the prior year, we found middle school mathematics teachers' current instructional vision to be related to their prior mathematical knowledge for teaching, their prior instructional practice, and their colleagues' prior instructional visions—with the strength of the relation depending on the density of teachers' advice networks. Based on these findings, we discuss implications for both inservice teacher professional development and preservice teacher education.